A Bulge in the Mid‐Left Cardiac Border: What Is the Diagnosis?. Issue 1 (18th September 2015) - Singhal, Anubhav; Kumar, Sudeep; Soni, Neetu; Kapoor, Aditya
Mini‐Abstract: Pseudoaneurysm of aorto‐mitral intervalvular fibrosa region (AMIVF) is relatively rare and leads to the development of a pulsatile cavity in the mitral–aortic junction communicating with LV outflow tract. We present a young man with a large AMIVF aneurysm in which the x‐ray revealed a prominent bulge on mid‐left cardiac border. The usual differential diagnosis of such a bulge includes an enlarged LA appendage, ruptured sinus of Valsalva aneurysm, dilated right ventricular subinfundibulum, absent pericardium, pericardial cysts, etc. Our case highlights the fact that physicians may also need to consider the rare possibility of an AMIVF aneurysm in this list.